2001
DOI: 10.4049/jimmunol.166.7.4578
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Transcriptional Activity of the Murine CD40 Ligand Promoter in Response to Signals Through TCR and the Costimulatory Molecules CD28 and CD2

Abstract: We have analyzed the murine CD40 ligand promoter with regard to stimulation of transcriptional activity in Jurkat T cells after signaling via the TCR and the costimulatory molecules CD28 and CD2. TCR engagement was necessary for the induction of transcriptional activity from the CD40 ligand promoter, and costimulation through either CD28 or CD2 further increased the activity. Analysis of promoter deletants showed that the DNA elements needed for transcriptional activity induced by costimulatory molecules were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 56 publications
6
32
1
Order By: Relevance
“…While studies using CD40L promoter driven reporters in both the mouse and human have found expression to be upregulated by CD28 costimulation, results from the majority of cellular studies in the mouse have been divided (28,29). Data from the CD28 knockout mouse clearly demonstrate that CD28 is not required for the induction or early (6 -10 h) expression of CD40L (26,30).…”
Section: Discussionmentioning
confidence: 94%
“…While studies using CD40L promoter driven reporters in both the mouse and human have found expression to be upregulated by CD28 costimulation, results from the majority of cellular studies in the mouse have been divided (28,29). Data from the CD28 knockout mouse clearly demonstrate that CD28 is not required for the induction or early (6 -10 h) expression of CD40L (26,30).…”
Section: Discussionmentioning
confidence: 94%
“…We found that FOXP3 also downregulated CD40L expression, a gene under the control of NFAT activity (22,34,43) that plays a critical role in the modulation of humoral and cellular immunity (35,44). CD40L expression is upregulated on naive CD4 + T cells via TCR stimulation in an Ag dose-dependent manner.…”
Section: Discussionmentioning
confidence: 97%
“…We do not know at the moment whether OX40 signaling induces directly or indirectly CD40L upregulation in Tem cells. Along T-cell activation, CD40L expression is induced by TCR ligation, and further enhanced by CD28 costimulation [60]. Less clear are the signals sustaining constitutive CD40L expression in memory T cells.…”
Section: Discussionmentioning
confidence: 99%